Grassroots Innovation in Village-Based Natural Resource Management in Lebak Regency - Rusman Nurjaman (BHUMI: Jurnal Agraria dan Pertanahan, 2022)
This study investigates the factors that encourage grassroots innovation that contributes to addressing natural resource management problems in Warungbanten Village. This study was conducted using a qualitative approach with a from the theoretical perspective of grassroots innovation. The primary data were obtained from observation during one-month field study and in-depth interviews with a number of key informants, such as village heads, traditional stakeholders, farmers, representatives of women's groups, and youth involved in the grassroots innovation process. The results showed that the growth of grassroots innovation in natural resource management in Warungbanten Village cannot be separated from three main factors, namely innovator aspect attached to the role of the village head as the initiator; socio-cultural and environmental aspect that allows the spirit of mutual cooperation and involvement of the parties; and market or benefit aspect attached to commercial and non-commercial values of the innovation carried out. Grassroots innovation that took place in Warungbanten Village also contributed to efforts to overcome challenges and problems in natural resource management, namely supporting the village sovereignty over natural resources, developing the sustainable livelihoods in rural areas, and removing administrative constraints in natural resource management caused by village boundary conflicts. Keywords: grassroots innovation, village natural resource management, village development